(untitled) - Whistman, Jonathan; Jonathan Whistman (Hoboken, 2016)
The Sales Boss reveals the secrets to great sales management, and provides direct examples of how you can start being that manager today. The not-so-secret "secret" is that a winning sales team is made up of high performers—but many fail to realize that high performance must be collective. A single star cannot carry the entire team, and it's the sales manager's responsibility to build a team with the right balance of skills, strengths, and weaknesses. This book shows you how to find the exact people you need, bring them together, and empower them to achieve more than they ever thought possible. You'll learn what drives high performance, and how to avoid the things that disrupt it. You'll discover the missing pieces in your existing training, and learn how to invest in your team to win. You'll come away with more than a better understanding of great sales management—you'll have a concrete plan and an actionable list of steps to take starting right now
Includes bibliographical references and index
Keywords: Sales management; Employee selection; Employees